Cause of death and cause-specific mortality for primary liver cancer in South Korea: A nationwide populationbased study in hepatitis B virus-endemic area - Bo Hyun Kim; Dahhay Lee; Kyu-Won Jung; Young-Joo Won; Hyunsoon Cho (Clinical and molecular hepatology, 2022)
Background/Aims: Primary liver cancer is one of the leading causes of cancer mortality worldwide. However, the causes of death have not been studied in detail in patients with liver cancer. Methods: The causes of death and cause-specific mortality risks in patients with primary liver cancer, diagnosed during 2000–2016, were investigated using the nationwide population-based cancer registry data in South Korea (n=231,388). The cumulative incidence function and Fine-Gray models were used to estimate the cause-specific mortality under the competing risks. Risks of non-cancer deaths relative to the general population were compared by standardized mortality ratios (SMRs). Results: Among 179,921 total deaths, 92.4%, 1.7%, and 6.0% of patients died of primary liver cancer, cancer from other sites, and non-cancer illnesses, respectively. Proportionate mortality from liver cancer remained high. The 5-year competing risks probability of death from liver cancer varied by tumor stage, from 42% to 94%, and it remained high 10 years after the diagnosis (61–95%). Competing mortality from other causes has continuously increased. The most common non-cancer causes of death were underlying liver diseases (SMR, 15.6; 95% confidence interval [CI], 15.1–16.1) and viral hepatitis (SMR, 46.5; 95% CI, 43.9–49.2), which demonstrated higher mortality risks compared to the Korean general population. Higher mortality risks of suicide (SMR, 2.6; 95% CI, 2.4–2.8) was also noted. Conclusions: Patients with liver cancer are most likely to die from liver cancer and related liver disease, even 10 years after the diagnosis, highlighting a need for specialized long-term follow-up care. KCI Citation Count: 0